Influencia de la suplementación proteica en las producciones del cerdo Ibérico en la Dehesa - LÓPEZ DE TORRE, GUILLERMO; BENITO HERNÁNDEZ, JOSÉ; FERRERA CLARAMONT, JOSÉ LUIS (Pastos, 1983)
The effect of adding 15 percent soybean meal to the summer cereal ration has been studied. Also the addition of 15 percent vs 5 percent soy- bean meal to a cereal mixture has been compared during the fattening period in the autumn when they were giving oak acorns under grazing conditions. Those effects were measured on weights at the end of sum- mer and fall, gains, feed effeciency and carcass characteristics. Four groups of 20 castrated pigs (10 males and 10 females) chosen at random were made. Average rate of gain was higher (460 vs 395 gr./day, p <^ 0,01) and food conversión was better (3,98 vs 4,64) for pigs receiving 15 percent soybean meal during summer. Protein contení of ration during fall while grazing on the oak fields did not affect gains. Carcass characteristics were not influenced by summer protein percent and, only some of them as carcass yield and back fat thickness were affected by fall protein percent. Sex affected all weights and gains considered. These results suggest that high protein rations during summer may result in improved productions at the end of the following acorn crop period. PASTOS
Keywords: aumento de peso; cerdo Ibérico (voyant); Montanera; suplementación de proteína